Fray Luis de León and the Crypto-Jewish Context of Antonio Enríquez Gómez’s El Noble Siempre es Valiente - Alexander John McNair (Religions)
The plays written by Fernando de Zárate, alias of the Crypto-Jewish poet Antonio Enríquez Gómez (1600–1663), appear on the surface to be militantly Catholic. Critics have struggled to reconcile the vision of the ‘Zárate’ plays, written in Seville after Enríquez’s clandestine return from exile (c. 1650), with the poems and treatises he penned in France (1636–1649), which were harshly critical of the Inquisition and Spanish notions of blood purity. One such play, El noble siempre es valiente [The nobleman is always brave], survives in an autograph manuscript from 1660. Written only months before the Inquisition identified and arrested Enríquez, the play became the most popular stage version of the epic hero El Cid in the eighteenth century, when it circulated under the titles El Cid Campeador and Vida y muerte del Cid [Life and death of El Cid]. The work stages the triumph of Spanish Christianity over Islam and appears to advocate an implacably bellicose ethos. This essay, however, interprets the play in the context of Enríquez’s exile writing, with specific focus on the influence of another erstwhile victim of the Inquisition, Fray Luis de León (1527–1591), whose works were found in the private libraries of Crypto-Jewish families.